2020
DOI: 10.9734/jamb/2020/v20i730259
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Methanolic and Methanolic-Aqueous Mixture Extract of Leaves of Plectranthus neochilus Schltr (Lamiaceae) and Bauhinia rufescens Lam (Fabaceae) on Two Strains of Enterobacteria Producing Beta-lactamases

Abstract: The objective of the study was to evaluate in vitro inhibitory effect of methanolic and methanolic-aqueous mixture extracts of Plectranthus neochilus Schltr (P. neochilus) and Bauhinia rufescens Lam (B. rufescens) on the growth of Escherichia coli 25922 and Proteus mirabilis. A phytochemical screening was carried out to highlight compounds (phenolic compounds, flavonoids, alkaloids) with antibacterial activity. Then, an antibiogram was Carried out to investigate the enzymes rendering the resistance. Finally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The hospital strain of Staphylococcus aureus and the reference strain (Staphylococcus aureus ATCC 25922) were all sensitive to the hydroethanolic extract of Bauhinia rufescens with a MIC of 12.5 mg/ml. Other work has also highlighted the sensitivity of Staphylococcus aureus to Bauhinia rufescens extracts with MICs varying according to the nature of the solvent used and my extraction method (14,10,5).…”
Section: Sensitivity Of Staphylococcus Aureusmentioning
confidence: 99%
See 1 more Smart Citation
“…The hospital strain of Staphylococcus aureus and the reference strain (Staphylococcus aureus ATCC 25922) were all sensitive to the hydroethanolic extract of Bauhinia rufescens with a MIC of 12.5 mg/ml. Other work has also highlighted the sensitivity of Staphylococcus aureus to Bauhinia rufescens extracts with MICs varying according to the nature of the solvent used and my extraction method (14,10,5).…”
Section: Sensitivity Of Staphylococcus Aureusmentioning
confidence: 99%
“…For hospital strains the MIC varies from 25 to 50 mg/ml depending on the part of the plant used. Many studies carried out throughout the world have confirmed the sensitivity of Escherichia coli to extracts of Bauhinia rufescens and Euphorbia hirta [3,15,13,14,10,5].…”
Section: Sensitivity Of Escherichia Colimentioning
confidence: 99%